Advances in intelligent IT : active media technology 2006 - Li, Yuefeng; Looi, Mark; Zhong, Ning, 1956- (Frontiers in artificial intelligence and applications, 2006)
Active Media Technology is an area of intelligent information technology and computer science that emphasizes the proactive roles of interfaces and systems. This book brings together papers from researchers from diverse areas, such as Web intelligence, data mining, intelligent agents, smart information use, networking and intelligent interface.